Menakar Partisipasi Pemilih Pemula dalam Pemilihan Kepala Daerah di Masa Pandemi Covid-19 - Khairunnisa Maulida; Hertanto Hertanto; Robi Cahyadi Kurniawan; Arizka Warganegara (PERSPEKTIF, 2022)
This article aims to measure the participation of novice voters in the regional head election during the Covid-19 pandemic in the election of mayor and deputy mayor in Bandar Lampung in 2020. The problem is focused on beginner voters who have a strategic position in the 2020 Bandar Lampung Election. beginners in the 2019 election is 20% of the total voter turnout as a whole. In order to approach this problem, Gabriel Almond's theoretical reference on forms of political participation is used. The data was collected through an online survey using google form and analyzed qualitatively. This study concludes that, first, 92% of respondents know that in December 2020 in Bandar Lampung there will be an election for Wakot and 79.5% of novice voters exercise their right to vote voluntarily. Second, 47.3% of novice voters have protested against policies made by the government and 70.5% of respondents did not participate in the public debate of the mayor and deputy mayor of Bandar Lampung in 2020. Third, novice voters in choosing a candidate for mayor and the deputy mayor is not influenced by money politics with a percentage of 96.4%. Fourth, 81.3% of novice voters answered that they were not influenced by their parents in using their right to vote and Awareness of novice voters using their right to vote as citizens was 97.3%.